Perinatal outcomes of frequent attendance in midwifery care in the Netherlands: a retrospective cohort study - Janneke T. Gitsels-van der Wal; Lisanne A. Gitsels; Angelo Hooker; Paula Scholing; Linda Martin; Esther I. Feijen-de Jong (BMC, 2020)
Abstract Background Over the last decade, a trend towards high utilisation of primary maternity care was observed in high-income countries. There is limited research with contradictory results regarding frequent attendance (FA) and perinatal outcomes in midwifery care. Therefore, this study examined possible associations between FA in midwifery care and obstetric interventions and perinatal outcomes. Methods A retrospective cohort study was performed in a medium-sized midwifery-led care practice in an urban region in the Netherlands. Frequent attenders (FAs) were categorised using the Kotelchuck-Index Revised. Regression analyses were executed to examine the relationship between FAs and perinatal outcomes, stratified by antenatal referral to an obstetrician. Main outcomes of interest were Apgar score ≤ 7 and perinatal death, birth weight, mode of delivery, haemorrhage, place of birth, transfer during labour, and a requirement for pain relief. Results The study included 1015 women, 239 (24%) FAs and 776 (76%) non-FAs, 538 (53%) were not referred and 447 (47%) were referred to an obstetrician. In the non-referred group, FA was significantly associated with a requirement for pain relief (OR 1.98, 95% CI 1.24-3.17) and duration of dilatation (OR 1.20, 95% CI 1.04-1.38). In the referred group, FA was significantly associated with induction of labour (OR 1.86, 95% CI 1.17-2.95), ruptured perineum (OR 0.50, 95% CI 0.27-0.95) and episiotomy (OR 0.48, 95% CI 0.24-0.95). In the non-referred and the referred group, FA was not associated with the other obstetric and neonatal outcomes. Due to small numbers, we could not measure possible associations of FA with an Apgar score ≤ 7 and perinatal death. Conclusion In our study, perinatal outcomes differed by FA and antenatal referral to an obstetrician. In the non-referred group, FA was significantly associated with medical pain relief and duration of dilatation. In the referred group, FA was significantly associated with induction of labour, ruptured perineum, and episiotomy. Further research with a larger study population is needed to look for a possible association between FA and primary adverse birth outcomes such as perinatal mortality.